Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 95608 by bobhans last updated on 26/May/20

Commented by john santu last updated on 26/May/20

another way  set x+y = h and xy = g  ⇒xy (x+y) = 30 & g + h = 11  ⇒gh = 30 ; g = 11−h  ⇒11h −h^2  = 30 ; h^2 −11h +30 =0  (h−6)(h−5) = 0

$$\mathrm{another}\:\mathrm{way} \\ $$$$\mathrm{set}\:{x}+{y}\:=\:{h}\:{and}\:{xy}\:=\:{g} \\ $$$$\Rightarrow{xy}\:\left({x}+{y}\right)\:=\:\mathrm{30}\:\&\:{g}\:+\:{h}\:=\:\mathrm{11} \\ $$$$\Rightarrow{gh}\:=\:\mathrm{30}\:;\:{g}\:=\:\mathrm{11}−{h} \\ $$$$\Rightarrow\mathrm{11}{h}\:−{h}^{\mathrm{2}} \:=\:\mathrm{30}\:;\:{h}^{\mathrm{2}} −\mathrm{11}{h}\:+\mathrm{30}\:=\mathrm{0} \\ $$$$\left({h}−\mathrm{6}\right)\left({h}−\mathrm{5}\right)\:=\:\mathrm{0} \\ $$$$ \\ $$$$ \\ $$

Commented by bobhans last updated on 26/May/20

thank you both

$$\mathrm{thank}\:\mathrm{you}\:\mathrm{both} \\ $$

Answered by john santu last updated on 26/May/20

⇒y = ((11−x)/(x+1))  x^2 (((11−x)/(x+1)))+x(((11−x)/(x+1)))^2 = 30  11x^3 −11x^2 −x^4 +121x = 30x^2 +60x+30  x_1 =1 & y_1  = 5  x_2  = 2 & y_2  = 3  x_3  = 3 & y_3  = 2  x_4  = 5 & y_4  = 1

$$\Rightarrow{y}\:=\:\frac{\mathrm{11}−{x}}{{x}+\mathrm{1}} \\ $$$${x}^{\mathrm{2}} \left(\frac{\mathrm{11}−{x}}{{x}+\mathrm{1}}\right)+{x}\left(\frac{\mathrm{11}−{x}}{{x}+\mathrm{1}}\right)^{\mathrm{2}} =\:\mathrm{30} \\ $$$$\mathrm{11}{x}^{\mathrm{3}} −\mathrm{11}{x}^{\mathrm{2}} −{x}^{\mathrm{4}} +\mathrm{121}{x}\:=\:\mathrm{30}{x}^{\mathrm{2}} +\mathrm{60}{x}+\mathrm{30} \\ $$$${x}_{\mathrm{1}} =\mathrm{1}\:\&\:\mathrm{y}_{\mathrm{1}} \:=\:\mathrm{5} \\ $$$${x}_{\mathrm{2}} \:=\:\mathrm{2}\:\&\:\mathrm{y}_{\mathrm{2}} \:=\:\mathrm{3} \\ $$$${x}_{\mathrm{3}} \:=\:\mathrm{3}\:\&\:\mathrm{y}_{\mathrm{3}} \:=\:\mathrm{2} \\ $$$${x}_{\mathrm{4}} \:=\:\mathrm{5}\:\&\:\mathrm{y}_{\mathrm{4}} \:=\:\mathrm{1}\: \\ $$

Answered by MJS last updated on 26/May/20

let x=p−q∧y=p+q   { ((p^2 +2p−q^2 −11=0)),((2p^3 −2pq^2 −30=0)) :}   { ((q^2 =p^2 +2p−11)),((q^2 =((p^3 −15)/p))) :}  p^2 +2p−11=((p^3 −15)/p)  p^2 −((11)/2)p+((15)/2)=0  p_1 =(5/2)∧p_2 =3  ⇒  q_1 =±(1/2)∧q_2 =±2  ⇒  (x=2∧y=3)∨(x=3∧y=2)∨       (x=1∧y=5)∨(x=5∧y=1)

$$\mathrm{let}\:{x}={p}−{q}\wedge{y}={p}+{q} \\ $$$$\begin{cases}{{p}^{\mathrm{2}} +\mathrm{2}{p}−{q}^{\mathrm{2}} −\mathrm{11}=\mathrm{0}}\\{\mathrm{2}{p}^{\mathrm{3}} −\mathrm{2}{pq}^{\mathrm{2}} −\mathrm{30}=\mathrm{0}}\end{cases} \\ $$$$\begin{cases}{{q}^{\mathrm{2}} ={p}^{\mathrm{2}} +\mathrm{2}{p}−\mathrm{11}}\\{{q}^{\mathrm{2}} =\frac{{p}^{\mathrm{3}} −\mathrm{15}}{{p}}}\end{cases} \\ $$$${p}^{\mathrm{2}} +\mathrm{2}{p}−\mathrm{11}=\frac{{p}^{\mathrm{3}} −\mathrm{15}}{{p}} \\ $$$${p}^{\mathrm{2}} −\frac{\mathrm{11}}{\mathrm{2}}{p}+\frac{\mathrm{15}}{\mathrm{2}}=\mathrm{0} \\ $$$${p}_{\mathrm{1}} =\frac{\mathrm{5}}{\mathrm{2}}\wedge{p}_{\mathrm{2}} =\mathrm{3} \\ $$$$\Rightarrow \\ $$$${q}_{\mathrm{1}} =\pm\frac{\mathrm{1}}{\mathrm{2}}\wedge{q}_{\mathrm{2}} =\pm\mathrm{2} \\ $$$$\Rightarrow \\ $$$$\left({x}=\mathrm{2}\wedge{y}=\mathrm{3}\right)\vee\left({x}=\mathrm{3}\wedge{y}=\mathrm{2}\right)\vee \\ $$$$\:\:\:\:\:\left({x}=\mathrm{1}\wedge{y}=\mathrm{5}\right)\vee\left({x}=\mathrm{5}\wedge{y}=\mathrm{1}\right) \\ $$

Answered by behi83417@gmail.com last updated on 26/May/20

x+y=a,xy=b  ⇒ { ((a+b=11)),((ab=30⇒z^2 −11z+30=0⇒z=5,6)) :}  ⇒ { ((x+y=5)),((xy=6⇒x^2 −5x+6=0⇒x∨y=2,3)) :}  ⇒ { ((x+y=6)),((xy=5⇒x^2 −6x+5=0⇒x∨y=1,5)) :}

$$\mathrm{x}+\mathrm{y}=\mathrm{a},\mathrm{xy}=\mathrm{b} \\ $$$$\Rightarrow\begin{cases}{\mathrm{a}+\mathrm{b}=\mathrm{11}}\\{\mathrm{ab}=\mathrm{30}\Rightarrow\mathrm{z}^{\mathrm{2}} −\mathrm{11z}+\mathrm{30}=\mathrm{0}\Rightarrow\mathrm{z}=\mathrm{5},\mathrm{6}}\end{cases} \\ $$$$\Rightarrow\begin{cases}{\mathrm{x}+\mathrm{y}=\mathrm{5}}\\{\mathrm{xy}=\mathrm{6}\Rightarrow\mathrm{x}^{\mathrm{2}} −\mathrm{5x}+\mathrm{6}=\mathrm{0}\Rightarrow\mathrm{x}\vee\mathrm{y}=\mathrm{2},\mathrm{3}}\end{cases} \\ $$$$\Rightarrow\begin{cases}{\mathrm{x}+\mathrm{y}=\mathrm{6}}\\{\mathrm{xy}=\mathrm{5}\Rightarrow\mathrm{x}^{\mathrm{2}} −\mathrm{6x}+\mathrm{5}=\mathrm{0}\Rightarrow\mathrm{x}\vee\mathrm{y}=\mathrm{1},\mathrm{5}}\end{cases} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com